Willingness To Pay Extra Charge For Increasing Safety While Using Public Transport Post Covid-19 Pandemic - Yacob, Najihah Mohamed (Universiti Sains Malaysia, 2022)
This study was conducted to investigate the willingness to pay extra charge for increasing safety while using public transport during post COVID-19 pandemic among Penangites. In this study, several parameters such as socio-demographic, frequency of using public transport, and intention to use public transport were examined to determine the significant factors that influence the willingness to pay towards PT’s operators initiatives to increase safety measures. Within two months period, the questionnaire surveys of 210 respondents were recorded for this study. The collected data were analyzed using descriptive analysis and statistical analysis through Statistical Package for the Social Science (SPSS). Pearson correlation was used to investigate the significant relationship between willingness to pay and sociodemographic factors of respondents. Next, Regression analysis was used in statistical analysis to determine factors that significantly influenced willingness to pay according to socio-demographic factors. From the results acquired through the regression analysis, the age, frequency of using public transport, and the intention to use public transport were factors that contribute to willingness to pay towards PT’s operators initiative.